Conservative Interventions for mobile Pes Planus in Adults: a systematic review - L Ashford, Robert; Mathieson, Ian; Rome, Keith (Revista Internacional de Ciencias Podológicas, 2016)
Background. Adult pes planus (flat foot) is a common problem encountered by many health care professionals. Despite the perception that flat foot can cause pain and impair function, and the availability and widespread use of various treatments, there is no consensus on the optimal treatment strategy. Aim. To assess the effectiveness of conservative (non-surgical) interventions for pes planus in adults. Method. A systematic search of the literature was undertaken. This included: the Cochrane Central Register of Controlled Trials; the CMSG Specialized Trials Register; an electronic search was conducted using MEDLINE (1960 to June 2012), EMBASE (1980 to June 2012), and CINAHL (1982 - June 2012). Specialised journals, trial reference lists and review articles were hand searched. Selection criteria: Randomised or quasi-randomised trials of treatment interventions for pes planus in adults. Trials that included specific pathologies such as plantar heel pain, metatarsal stress fractures, posterior-tibial tendon dysfunction, ankle fractures, rheumatoid foot pathologies, neuromuscular conditions and diabetic foot complications were excluded. Data collection and analysis: Two authors independently screened the search results to identify those meeting the inclusion criteria and quality assessed those included using a checklist based on the Cochrane Collaboration Assessment of Risk of Bias tool. This tool focused on risk of selection, performance, detection, attrition and reporting bias. Results. Four trials, involving 140 subjects, met the inclusion criteria for the review. All four were judged to be at high risk of bias in at least one area, and were also at unclear risk of bias in at least one other area. All scored highly in relation to attrition bias, due to the short follow up times and experimental designs used. Data was not pooled due to the high level of heterogeneity identified in the interventions assessed, participants selected and outcomes measured. The results of one study suggest that after four weeks of use orthoses may result in a significant improvement in medio lateral sway, and may result in improved, although non-significant, general foot-related quality of life (Rome 2004). One study (Redmond 2009) suggests that their effect on plantar pressure distribution in the foot may not be dependent on whether they are custom or prefabricated devices. Although this study identified significant changes in some plantar pressure variables with both custom and prefabricated devices, another (Esterman 2005) failed to find any significant effect of ¾ length prefabricated orthoses on pain, injury incidence, foot health or quality of life in a group of air force recruits. The fourth study (Jung 2009) suggests that exercising the intrinsic foot muscles may enhance the effect of orthoses. Despite these findings, since each study incurred risk of bias in at least one area no conclusions can be drawn.